Optical Properties of Nanoporous Silicon in the Presence of Magnetic Nanostructures. (19th June 2018) - Granitzer, Petra; Rumpf, Klemens; Poelt, Peter; Reissner, Michael
Abstract : This work aims to combine luminescent microporous silicon with a ferromagnetic metal to create a nanocomposite system with modifiable photoluminescence due to the presence of metal deposits as well as to influence the optical behavior by an external magnetic field. Due to the metal filling of the porous silicon (PSi) the peak of the photoluminescence is blue-shifted and furthermore an increase of the intensity is observed. Magnetic characterization of the samples shows a film-like behavior with the magnetic easy axis parallel to the surface which is due to interconnections of the metal deposits. The influence of the magnetic metal filling on the optical properties is discussed and the magnetic characterization of the samples is presented.